2017
DOI: 10.18203/2320-1770.ijrcog20174986
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum ultrasound to predict vaginal labor: a prospective cohort study

Abstract: Background: Non-invasive transperineal ultrasound has been used to detect the descent of the fetal head using head-perineum distance (HPD) and angle of progression (AOP). The aim was to evaluate HPD and AOP as predictors of vaginal delivery in the first stage of labor.Methods: This was a prospective cohort study in Riga Maternity Hospital in Latvia from May till August 2016. The study included only nulliparous women with singleton pregnancies and cephalic presentation. Ultrasound was used to measure HPD and AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…First, the aim of the paper was to achieve a synthesis of the sensitivity, specificity, positive predictive value, and negative predictive value, which may limit the analyses of the different research methods adopted. Next, in this review, there are eight studies from the same African country, and because there are different healthcare institutions, ultrasound systems and observers in conducting births may have contributed to the variability of the results [ 36 , 44 ]. Moreover, pelvic shapes and sizes differ with ethnicity, which may result in different results in the accuracy of labor assessment.…”
Section: Discussionmentioning
confidence: 99%
“…First, the aim of the paper was to achieve a synthesis of the sensitivity, specificity, positive predictive value, and negative predictive value, which may limit the analyses of the different research methods adopted. Next, in this review, there are eight studies from the same African country, and because there are different healthcare institutions, ultrasound systems and observers in conducting births may have contributed to the variability of the results [ 36 , 44 ]. Moreover, pelvic shapes and sizes differ with ethnicity, which may result in different results in the accuracy of labor assessment.…”
Section: Discussionmentioning
confidence: 99%
“…27 Were able to predict vaginal delivery during 1 st stage of labour dystocia with angle of progression <100 o (76% ROC/AUC) and head perineum distance >5 cm (81% ROC/ AUC) increase the chance of cesarean section. 28 Determined the predictive value of vaginal delivery are with angle of progression >105 o (87.7% ROC/AUC) and head perineum distance < 4 cm (86.5% ROC/AUC) 29 .…”
Section: Discussionmentioning
confidence: 99%
“…37 HPD less than 40 mm in the first stage of active labor has also been confirmed by others as a cut-off for high chance of a vaginal delivery. 38 Hamilton et al studied the relation between clinically assessed cervical dilatation and head station and found a linear association, but an ultrasound study found that this association was not linear. 39 Fetal station was initially stable and accelerated during the last four hours in women ending with a spontaneous delivery.…”
Section: Ultrasound Assessment Of Fetal Stationmentioning
confidence: 99%